A Study to Assess the Relationship of Anthropometric Indices to Risk of Obstructive Sleep Apnea among Patients Attending Pulmonology Outpatient Department at GKNM Hospital, Coimbatore - C, Meenakumari; Latif, Abdul (Indian Journal of Nursing Sciences, 2024)
Aim: The study aimed to assess the relationship of anthropometric indices to risk of obstructive sleep apnea (OSA) among patients attending pulmonology outpatient department (OPD) at GKNM Hospital, Coimbatore. Materials and Methods: The research was conducted using a descriptive research design and the sample size was set at one hundred people who were chosen using a non-probability convenient sampling technique. The participants’ demographic information was collected and the Modified Berlin Questionnaire was used to determine the participants’ potential for developing OSA. An anthropometric measurement system that is standardized was utilized for the purpose of determining anthropometric indices. Results: Descriptive and inferential statistics were used to analyze the data. The relationship between anthropometric indices and risk of OSA was calculated using single mean t-test method. The study findings indicate that there is a significant relationship between the anthropometric indices such as body mass index (BMI), body fat percentage (BFP), neck circumference (NC) and waist-hip ratio (WHR), and risk of OSA. Conclusion: The results of the study demonstrated that there is a relationship between the danger range of anthropometric indices, including BMI, BFP, NC, and WHR, and the risk of OSA in patients who were attending the pulmonology OPD. Therefore, patients who are at risk of developing OSA can assist prevent the condition from developing early on if they are recognized at an early stage and basic preventative measures are performed.